Experimental and numerical investigation on interlayer fracture process of roller compacted concrete. (1st August 2022) - Luo, Danni; Lu, Sihang; Hu, Cheng; Xue, Zixi
Highlights: A peridynamic BQMI model is proposed for the fracture processes of RCC interfaces. Three-point bending tests of variously prepared RCC specimens were conducted. The fracture toughness and fracture energy of RCC interlayers were analysed. The AE characteristics and its precursors of RCC interlayer fracture were analysed. Good agreement was observed between the simulation and experimental results. Abstract: A roller-compacted concrete (RCC) is a dry concrete with zero slump, and it is constructed in layers. The interlayers of RCC dams are generally weak. The fracture properties of the RCCs affect the performance and safety of the dam structures. Herein, fracture tests on RCC three-point bending beams were conducted, and the fracture toughness and energy of the RCC interlayers under different time intervals and interlayer treatments were studied. The acoustic emission (AE) characteristics of the interlayer fracture behaviours were analysed. Additionally, a bond-based quasi-brittle material interface (BQMI) model for peridynamics was constructed for interlayer fracture analysis, and the numerical results of the interlayer fracture process of the RCCs were compared with the test results. The results proved that longer interval times lowered the fracture toughness and energy. Moreover, interlayer roughening and cement mortar addition improved the interlayer fracture properties. Crack initiation and unstable failure could be identified or predicted by the abrupt changes in the AE hits and accumulative absolute AE energy, the appearance of AE time–frequency quiet period, and changes in AE frequency distribution and dominant frequency ratio. Furthermore, the peridynamic numerical simulation results were in good agreement with the RCC test results, demonstrating the reasonableness and effectiveness of the BQMI model. This method shows good performance in reconstructing the entire fracture process of the RCC interlayers.